Context‐dependent latent inhibition in preweanling rats. Issue 7 (11th September 2014) - Revillo, D.A.; Gaztañaga, M.; Aranda, E.; Paglini, M.G.; Chotro, M.G.; Arias, C.
ABSTRACT Preexposure to a conditioned stimulus (CS) usually weakens conditioning, an effect known as latent inhibition. Similar to other learning interference effects, latent inhibition has been characterized as context‐dependent, which means that the magnitude of this effect can be attenuated by changing the context between the different phases of the procedure (e.g., preexposure and conditioning). Latent inhibition has been found with a variety of procedures in infant rats, but the few studies that examined the context‐dependency of this phenomenon during this ontogenetic period found no context‐change effect. The present study explored the context‐dependency of latent inhibition during infancy using a conditioned taste aversion preparation and employing contexts enriched with distinctive odors to increase the possible efficacy of the context manipulation. Experiment 1 showed that three preexposures to the CS (saccharin) were sufficient to retard conditioning to the same CS, although this effect was also observed in a control group preexposed to an alternative taste stimulus (saline), in comparison with a non‐preexposed control group. In Experiment 2a, the CS‐preexposure effect was found to be specific to the preexposed CS when the number of preexposures was increased. This effect was revealed as context‐dependent in Experiment 2b, since it was attenuated by changing the context between preexposure and conditioning. The present result is consistent with recent studies showing the context‐dependency of extinction in preweanling rats, thus demonstrating these animals' capacity to learn about context early on in their development. © 2014 Wiley Periodicals, Inc. Dev Psychobiol 56: 1507–1517, 2014.